Efficacy of Commonly Used Anti-coccidial Drugs against Coccidiosis in Buffalo Calves - Navkar, Aniket B.; Khillare, Bapurao S.; Shirale, Sridhar Y.; Narladkar, Babasaheb W.; Bhangale, Gajendra N. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was designed to evaluate the efficacies of commonly used anti-coccidial drugs viz. Sulphadimidine, Amprolium and  Toltrazuril against coccidiosis in buffalo calves. Eighteen buffalo calves under 6 months of age naturally infected with coccidiosis were  randomly divided into three groups (6 calves each). Calves were administered with standard doses, and the efficacy of drugs were  assessed by observing the oocysts per gram of feces and weight gain. It was observed that all three treatments showed a significant  impact in treating coccidiosis and weight gain. Toltrazuril appeared to be comparatively more efficacious than sulphadimidine and  amprolium in terms of reduction in OPG and weight gain. However, amprolium and sulphadimidine showed faster efficacy than toltrazuril  in reducing the coccidial burden in buffalo calves
Keywords: Amprolium Buffalo calves; Coccidia; Drug efficacy; Sulphadimidine; Toltrazuril